Comparison of degree of sexual dysfunction by using female sexual functional index-6 in the subfertile and other females presenting to tertiary care hospital - sadiq, Hasina; Fatima, Shafaq; Sohail, Irum; Aslam, Maria; Habib, Filza; Naz, Falak (Journal of the Pakistan Medical Association, 2025)
Objectives: To compare the prevalence of sexual dysfunction between subfertile females and the general population, and to check the validity of the translated modified version of the Female Sexual Functional Index Score in Pakistani population. Method: The cross-sectional, prospective, comparative, analytical study was conducted February to July 2023 at the Shifa College of Medicine Hospital and the Kahuta Research Laboratories Hospital, Islamabad, and comprised females aged 18-40 years who had been sexually active for at least 4 preceding weeks. Subfertile women were placed in group A, while group B had normal women. Data was collected using the translated version of the Female Sexual Functional Index Score, limited to only 6 of the total 19 questions (Nos 2, 4, 7, 11, 16 and 17) to assess the female sexual dysfunction covering all the six domains of desire, arousal, lubrication, orgasm, satisfaction and pain. The total score ranged 2-30, with lower scores indicating worse sexual function. The cutoff point was 19, with <19 considered an indication of sexual dysfunction. Data was analysed using SPSS 23. Results: Of the 276 patients, 138(50%) were in each of the two groups. The overall mean age was 31.5±4.1 years. Mean score was 19±3.4. There was a significant difference in the scores between groups A 17.53±2.98 and B 20.4±3.26 (p<0.001). Patients with polycystic ovary syndrome had a higher mean score of 18.47±2.4, while those with endometriosis had mean score 15.91±3.4. Conclusion: The prevalence of sexual dysfunction in the subfertile group was noted. The translated modified version of the Female Sexual Functional Index Score was fund to be a valid tool with moderate reliability for the assessment of sexual dysfunction in Pakistani women. Key Words: Infertility, Sexual satisfaction, Sexual dysfunction.